2009
DOI: 10.1074/jbc.m901177200
|View full text |Cite
|
Sign up to set email alerts
|

The Armadillo Repeat-containing Protein, ARMCX3, Physically and Functionally Interacts with the Developmental Regulatory Factor Sox10

Abstract: Sox10 is a member of the group E Sox transcription factor family and plays key roles in neural crest development and subsequent cellular differentiation. Sox10 binds to regulatory sequences in target genes via its conserved high mobility group domain. In most cases, Sox10 exerts its transcriptional effects in concert with other DNA-binding factors, adaptor proteins, and nuclear import proteins. These interactions can lead to synergistic gene activation and can be cell type-specific. In earlier work, we demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 67 publications
4
35
0
Order By: Relevance
“…Several members, including Alex3, have nuclear localization in neurons. This observation is consistent with a previous study showing interaction of Alex3 with the transcription factor Sox10 and enhancement of its transcriptional activity by Alex3 22 . These observations support that Armcx genes have biological functions in two compartments (namely, mitochondria and nucleus), as has been shown for other proteins, including Sox10, DISC1 and HDAC1 [39][40][41] .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Several members, including Alex3, have nuclear localization in neurons. This observation is consistent with a previous study showing interaction of Alex3 with the transcription factor Sox10 and enhancement of its transcriptional activity by Alex3 22 . These observations support that Armcx genes have biological functions in two compartments (namely, mitochondria and nucleus), as has been shown for other proteins, including Sox10, DISC1 and HDAC1 [39][40][41] .…”
Section: Discussionsupporting
confidence: 94%
“…2e,f). These observations are consistent with a previous study reporting Alex3 protein in outer membrane mitochondrial fractions 22 .…”
Section: Armcx and Armc10 Genes Encode For Mitochondrial Proteinssupporting
confidence: 94%
See 1 more Smart Citation
“…Though the classical ARM family was involved in a variety of processes such as cell adhesion, embryogenesis and tumorigenesis (Peifer et al, 1994;Hatzfeld, 1999), little is known about the ALEX genes. Recent report demonstrates that the ALEX3 directly interacts with the sex determining region Y (Sry)-box 10 (SOX10) transcription factor via the ARM repeat domains and alters its subcellular localization and transcriptional activity (Mou et al, 2009). In addition, the study have shown that the ALEX3 gene encodes a mitochondrial-targeted protein and the non-canonical Wnt/PKC pathway regulates mitochondrial distribution through ALEX3 protein degradation (Serrat et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…their amino (n)-terminal region harbors a transmembrane domain, suggesting that these proteins may localize at membrane structures in cells. recently, armcx3 was revealed as an integral membrane protein of the mitochondrial outer membrane that functionally interacts with the transcriptional regulator Sox10 (4). in addition, ARMCX4, ARMCX5 and ARMCX6, the localizations of which have been mapped to chromosome regions xq22.1, xq22.1-q22.3 and Xq21.33-q22.3, respectively, were also identified.…”
Section: Introductionmentioning
confidence: 99%